2013
DOI: 10.1080/02772248.2013.790970
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric particulate matter in Nigerian megacities

Abstract: The paucity of data on air pollution indices in Nigeria prompted us to commence a national screening exercise regarding particulate matter loads. Six potential megacities (Aba, Abuja, Lagos, Kano, Maiduguri, and Port-Harcourt) representing the six geographical zones in Nigeria were chosen for the study. Sampling was achieved using a 'Gent' stacked filter unit sampler capable of collecting fractions of particulate matter with sizes of <10-mm and <2.5-mm simultaneously. The mean values for PM 10 are 550, 35, 87,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 8 publications
5
27
1
Order By: Relevance
“…This is in line with the observations of Efe (2008), the author examined the spatial distribution of particulate air pollution in Nigeria cities and reported that 70% of the cities studies have values above the daily and annual mean recommended by WHO. Works of Ezeh et al (2012) and Obioh et al (2013) also corroborate the levels of PM 2.5 observed from the dataset used for this study. There are serious implications for human health with this level of ambient air quality, especially since PM 2.5 has been implicated in many pulmonary and cardiovascular problems.…”
Section: Resultssupporting
confidence: 70%
“…This is in line with the observations of Efe (2008), the author examined the spatial distribution of particulate air pollution in Nigeria cities and reported that 70% of the cities studies have values above the daily and annual mean recommended by WHO. Works of Ezeh et al (2012) and Obioh et al (2013) also corroborate the levels of PM 2.5 observed from the dataset used for this study. There are serious implications for human health with this level of ambient air quality, especially since PM 2.5 has been implicated in many pulmonary and cardiovascular problems.…”
Section: Resultssupporting
confidence: 70%
“…The incidence of TAD on the environ had significant effects on the residents due to complaints of low visibility and dust depositions on buildings, vehicles, and crops. In comparison, of this study results with those obtained by Obioh et al (2013) for Nigerian mega cities, it was observed that the values of the cities like Aba (422 -926 µg/m 2 ), Maiduguri (37 -370 µg/m 2 ) and Kano (61 -757 µg/m 2 ) were far above the results of this study. The reasons for the differences could be attributed to the higher traffic densities of the study areas, again Maiduguri and Kano are closer to Saharan desert, which is closer to dust.…”
Section: Resultscontrasting
confidence: 50%
“…In contrast to cities in the developed economies, there is a dominance of the coarse-mode fraction in the atmospheric aerosol loading in major Nigerian cities. This has been attributed to frequent and persistent resuspension of dust from the large expanse of unpaved roads [Akinlade et al, 2015;Obioh et al, 2013;Owoade et al, 2013].…”
Section: 1002/2016jd025584mentioning
confidence: 99%
“…This lower AE values are attributable to dust resuspension from the predominantly unpaved and damaged paved road networks that lie across major cities in Nigeria. Several in situ PM measurements across various site classifications (residential, marine, heavy traffic, and industrial) in major Nigeria cities have reported the dominance of the coarse-mode (PM 2.5-10 ) PM fraction [Akinlade et al, 2015;Ezeh et al, 2012;Obioh et al, 2013;Owoade et al, 2013].…”
Section: Biomass Burning (Bb) Aerosol Clustermentioning
confidence: 99%